NORARTOCARPETIN, FLAVONE DERIVATIVE FROM LEAVES OF Artocarpus fretessi - Nunuk Hariani Soekamto; Nursiah La Nafie; Fredryk Welliam Mandey; Marry Garson (Universitas Gadjah Mada, 2009)
Norartocarpetin (1), together with mulberrin (2) and mulberrokromen (3) were isolated from Artocarpus fretessi (Moraceae). This plant is an endemic species in Indonesia and locally known as